Assessment and Predicting Factors of Repeated Brain Computed Tomography in Traumatic Brain Injury Patients for Risk-Stratified Care Management: A 5-Year Retrospective Study - Preeda Sumritpradit; Thitipong Setthalikhit; Sorayouth Chumnanvej (Neurology Research International)
Background and Objective. To determine the value of repeated brain CT in TBI cases for risk-stratified care management (RSCM) and to identify predicting factors which will change the neurosurgical management after repeated brain CTs. Methods. A 5-year retrospective study from January 2009 to August 2013 was conducted. The primary outcome was the value of repeated brain CT in TBI cases. The secondary outcome is to identify predicting factors which will change the neurosurgical management after repeated brain CTs. Results. There were 145 consecutive patients with TBI and repeated brain CT after initial abnormal brain CT. Forty-two percent of all cases (N=61) revealed the progression of intracranial hemorrhage after repeated brain CT. In all 145 consecutive patients, 67.6% of cases (N=98) were categorized as mild TBI. For mild head injury, 8.2% of cases (N=8) had undergone neurosurgical management after repeated brain CT. Only 1 from 74 mild TBI patients with repeated brain CT had neurosurgical intervention. Clopidogrel and midline shift more than 2 mm on initial brain CT were significant predicting factors to indicate the neurosurgical management in mild TBI cases. Conclusion. Routine repeated brain CT for RSCM had no clinical benefit in mild TBI cases.